(untitled) (Dermatology Reports, 2025)
Merkel cell carcinoma (MCC) is a rare, aggressive neuroendocrine skin tumor, mainly linked to Merkel Cell Polyomavirus (MCPyV) and less often to ultraviolet exposure. Additional risk factors include advanced age and immunosuppression. Although MCC is known to grow rapidly, its exact growth rate has not been described yet. We report a case of a 73-year-old man who developed de novo MCC on the lower eyelid while undergoing immunotherapy with nivolumab. Clinical photographs document the absence of disease in March 2024 and the appearance of a 7 mm papule in October 2024. Histology confirmed the diagnosis. This case represents rare visual evidence of MCC’s rapid progression, suggesting an estimated growth rate of approximately 1 mm/month. A controversial aspect is that MCC developed despite ongoing treatment with a PD-1 checkpoint inhibitor, currently recommended for this cancer. Although anecdotal, this case highlights MCC’s progression and the need for further research and new therapies.